2017
DOI: 10.1371/journal.pone.0184485
|View full text |Cite
|
Sign up to set email alerts
|

Training discrimination diminishes maladaptive avoidance of innocuous stimuli in a fear conditioning paradigm

Abstract: Anxiety disorders are the most common mental disorder worldwide. Although anxiety disorders differ in the nature of feared objects or situations, they share a common mechanism by which fear generalizes to related but innocuous objects, eliciting avoidance of objects and situations that pose no objective risk. This overgeneralization appears to be a crucial mechanism in the persistence of anxiety psychopathology. In this study we test whether an intervention that promotes discrimination learning reduces general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Based on the finding that stronger fear generalization is linked to a misperception of stimuli with high perceptual similarity in healthy participants and patients with generalized anxiety disorder (Laufer et al, ; Struyf et al, ), one approach is directed toward the improvement of perceptual discrimination processes. Lommen et al () showed that a discrimination training reduced avoidance behavior to generalization stimuli in healthy participants, although the explicit expectation of threat was not reduced. Whether such an approach is beneficial in PTSD has to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the finding that stronger fear generalization is linked to a misperception of stimuli with high perceptual similarity in healthy participants and patients with generalized anxiety disorder (Laufer et al, ; Struyf et al, ), one approach is directed toward the improvement of perceptual discrimination processes. Lommen et al () showed that a discrimination training reduced avoidance behavior to generalization stimuli in healthy participants, although the explicit expectation of threat was not reduced. Whether such an approach is beneficial in PTSD has to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of fear overgeneralization in anxiety disorders makes it an ideal candidate to be targeted in interventions (Lissek, ). As deficits in perceptual discrimination are central factors in fear overgeneralization, recent attempts have been made to improve individuals’ perceptual discrimination abilities through the use of novel training tasks with a primary goal of moderating fear overgeneralization (Ginat‐Frolich, Klein, Katz, & Shechner, , Ginat‐Frolich, Gendler, Marzan, Tsuk, & Shechner, ; Lommen et al, ). However, no previous studies have examined the effect of perceptual discrimination training on fear overgeneralization and avoidance among highly anxious individuals.…”
Section: Introductionmentioning
confidence: 99%
“…As perception is a core component of stimulus classification, perceptual discrimination has been suggested as a possible moderator for fear overgeneralization (Struyf, Zaman, Hermans, & Vervliet, ; Struyf, Zaman, Vervliet, & Van Diest, ). Two previous studies, both conducted with healthy adults, assessed two different novel perceptual discrimination training tasks aimed to improve perceptual discrimination and decrease fear overgeneralization (Ginat‐Frolich et al, , Lommen et al, ). Lommen et al () found that, as compared with a control condition, participants in the training group showed less avoidance of GSs perceptually similar to the safety cue, though no between‐group differences emerged in self‐reported fear generalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing fear generalization while maintaining adaptive fear responses will reduce the daily burden experienced by individuals living with these disorders. Recently, introducing procedures that involve stimulus discrimination into cognitive behavioral therapy has been shown to reduce fear generalization, re-experiencing and intrusive thoughts in PTSD patients (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%